Pengaruh Pengembangan Karir, Disiplin Kerja, Lingkungan Kerja, Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Dinkes Purbalingga - Sevina Putri Rahayu; Sri Sundari; Harsuti Harsuti (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research is based on the gap phenomenon in the form of employees being late and leaving early which is still experiencing fluctuations. This condition can be shown through data on the number of employees who are late and leave early at the Purbalingga Regency Health Service and research gaps in the form of differences in research results. The aim of this research is to analyze the partial influence of career development, work discipline, work environment and work motivation on job satisfaction of Purbalingga District Health Service employees. The population in this study were ASN employees of the Purbalingga District Health Service, totaling 98 people with a sample of 88 respondents. The data analysis method used is multiple linear regression and hypothesis testing using t test calculations. The results of this research show career development, work discipline, work environment, and work motivation influence employee job satisfaction. The implication of this research is that the Purbalingga District Health Service needs to provide career clarity for employees, make more efforts to improve good relations between co-workers, improve employee safety, pay more attention to the rewards given to employees according to the work they do.